Influences of yellow and green lights on the visual response of western flower thrips and field verification - Liu, Qihang; Zhao, Mingqian; Miao, Jin; Fu, Guangchun; Wu, Yuqing (International Journal of Agricultural and Biological Engineering, 2023)
This study aimed to determine the effects of spectral light characteristics on the visual response of the western flower thrips, the strengthening mechanism of thrips response behavior regulated by light, and thrips response characteristics to contrast light. Light with combined and single wavelength were tested by using a self-made behavior response device for thrips. Light sources for trapping thrips were made to verify the trapping effect on thrips in a greenhouse, and the reasons for changes in thrips behavior were analyzed to characterize the mechanism of their phototactic response. The results showed that the light mode (single, contrast, combined light) affected the thrips visual response and approach response, whereas in contrast light, the effects were optimal. Combination light inhibited the thrips visual response, and when the illumination increased, the thrips visual response to single and combination light intensified, and the thrips approach sensitivity to green light increased in contrast and combination light. However, the light mode did not affect the thrips visual response and sensitivity to spectral light characteristics. The degree of thrips visual response to yellow light was stronger than that to green light, while the degree of thrips visual response to green light was stronger than that to yellow light, indicating that the photo-induced mechanism of the thrips visual response differed from that of the thrips approach response. Moreover, in the greenhouse, the trapping effect of different light sources on thrips was positively correlated with temperature. The trapping effect of green light was optimal, followed by a yellow light source, while the difference of light intensity (illumination, illumination energy) and its photo-thermal intensity between yellow and green light was the reason for the differences in the degree of visual trends and the trapping effects of thrips. However, the sensitivity of thrips responding to different light depended on the difference in the heterogeneous stimulation intensity of different spectral light. Thus, light brightness and photo-thermal effects were the causes of thrips visual responses, while bio-photoelectric reaction effects caused thrips to produce a visual response and affected the degree of the thrips visual response. The results reveal the underlying causes of pest control by light, and provide a theoretical basis for the research and development of pest induction equipment and light arrangements.Keywords: pest control, western flower thrips, yellow and green light, visual response, field verification, light modeDOI: 10.25165/j.ijabe.20221504.6432Citation: Liu Q H, Zhao M Q, Miao J, Fu G C, Wu Y Q. Influences of yellow and green lights on the visual response of western flower thrips and field verification. Int J Agric & Biol Eng, 2022; 15(4): 49–56.